Treatability of organic matter derived from surface and subsurface waters of drinking water catchments. (February 2016) - Awad, John; van Leeuwen, John; Liffner, Joel; Chow, Christopher; Drikas, Mary
Abstract: The treatability of NOM present in runoff and subsurface waters from discrete zero-order catchments (ZOCs) with three land management practices (Australian native vegetation, pine plantation, grasslands) on varying soil textures of a closed drinking water reservoir-catchment was investigated. Subsurface water samples were collected by lysimeters and shallow piezometers and surface waters by installation of barriers that diverted waters to collection devices. For small sample volumes collected, a 'micro' jar testing procedure was developed to assess the treatability of organics by enhanced coagulation using alum, under standardised conditions. DOM present in water samples was quantified by measurement of DOC and UV absorbance (at 254 nm) and characterized using these and F-EEM. The mean alum dose rate (mg alum per mg DOC removed or Al/DOC) was found to be lower for DOM from sandy soil ZOCs (21.1 ± 11.0 Al/DOC) than from clayey soil ZOCs (38.6 ± 27.7 Al/DOC). ZOCs with Pinus radiata had prominent litter layers (6.3 ± 2.6 cm), and despite differences in soil textures showed similarity in DOM character in subsurface waters, and in alum dose rates (22.2 ± 5.5 Al/DOC). For sandy soil ZOCs, the lowest alum dose rates (16.5 ± 10.6 Al/DOC) were for waters from native vegetation catchment while, for clayey soil ZOCs, waters from pine vegetation had the lowest alum dose rates (23.0 ± 5.0 Al/DOC). Where ZOCs have a prominent O horizon, soil minerals had no apparent influence on the treatability of DOM. Highlights: DOM not complexed with clay is less amenable to removal by alum. Lowest alum dose rates were for waters from native vegetation on sandy soil. Soil-water from prominent O horizon sites show similarity in DOM treatability.